In Silico Analysis of Advanced Processing Methods for Light-weight Alloys Powders - (:unkn) unknown (My University, 2018)
Light-weight Al and Mg-based metal-matrix nanocomposites (MMNCs) are lauded as one of the most promising structural materials for vehicle, military, and construction applications. These MMNCs are often synthesized using the powder metallurgy (PM) process under liquid nitrogen cryogenic environments to control the grain sizes. It is believed that proper incorporation of the nitrogen species into the bulk lattice during processing could strongly enhance the mechanical properties of MMNCs by forming N-rich dispersoids. In this work, using the density-functional theory (DFT), the adsorption, absorption and diffusion behavior of nitrogen molecule/atoms have been studied and related to t Al and Mg MMNC PM processing. The study includes the impacts of binding sites, alloying elements (Al, Zn, and Y in Mg and Mg, Mn and Fe for Al), and surface crystallographic planes on the nitrogen molecule adsorption energies. The transition state (TS) behaviors for the bond breaking and lattice diffusion of nitrogen were examined. The results show that in presence of Mg (0001) or Al (111) surfaces, dissociation of $N_2$ to N atoms requires 1/9 to 1/5 of the isolated state energy , respectively. As a critical issue limiting the application of Mg-based MMNCs, the degradation (corrosion) of Mg alloys in aqueous media was modeled in this work. It is known that both the internal crystal structures and the impurity compositions/contents in the Mg alloys can affect the degradation rates. Density-functional theory (DFT) computation was utilized to understand the surface degradation behaviors with different crystallographic orientations and impurity elements from an atomistic standpoint. The adsorption response of the Mg alloy surface to the water molecule and the dissolution of surface atoms were studied to describe the degradation behavior of Mg and Mg alloys. The tendency for water molecule adsorption was quantified for Mg-based slab systems with low-index surface planes and various alloying elements including Al, Zn, Ca, and Y. The trends for surface degradation from these systems were examined using surface energy analysis and electrode potential shift analysis. The results showed that adding Ca and/or Y increases the propensity to attract a water molecule to the alloy surface. Also, it was generally found that the relative electrode potential shift of Mg-Y alloys is positive while those of all other alloys are negative. After having a comprehensive understanding about the atomistic behavior of metal powder in contact with the cryomilling media, the consolidation process was analyzed, including the melting and resolidification of powder through selective laser melting. At this stage of the work the concerns were to achieve the maximum connectivity between the powder layers after resolidification and to avoid extreme superheat. Since the efficiency of the MMNCs strongly relies on homogeneous distribution of reinforcement particles the SLM process was optimized to avoid any clustering of the reinforcement particles. Focusing on consolidation of MMNCS, Al10SiMg/AlN with weight ratio of 99:1 was chosen. AlSi10Mg with $10\%$ Si and $0.5\%$ Mg is one the most convenient compositions among the light weight alloys for laser melting processes, due to its narrow solidification range, that provides sufficient fluidity to produce sound products. Also, as the powder had been prepared via cryomilling process, the presence of AlN particles was proven based on the DFT calculations and experimental evidence described earlier. The laser power, scanning velocity and initial temperature of the powder were selected as the most important factors affecting the melting and solidification of the alloy powder. Finite volume analysis and experimental design were applied to optimize the SLM processing condition. Finite volume method was used to estimate the melt pool geometry, temperature profile of the part and velocity of solidification front. This information is necessary to produce strong parts with homogeneous properties all over the specimen, minimize energy consumption and avoid formation of defects in the sample. It was confirmed that even in the most extreme conditions the maximum temperature during the process would not exceed 1710K, which is roughly 460K below the melting temperature of the AlN reinforcement particles. The laser speed and power have significant effect on the melt pool geometry and maximum temperature of melt pool while the effect of initial powder temperature was insignificant for both of the response values. The AlN reinforcement particles are expected to have a homogeneous distribution since the velocity of the solidification front is higher than the critical calculated value of 5900 $\mu$ m/s. Results also showed that the solidification front velocity depends on the laser speed and the effects of laser power and initial temperature are insignificant. This work provides a comprehensive multiscale computational model tracking the Al and Mg based light-weight alloys from powder preparation stage to shaping the final product that considers potential gaps with focus on solidification process. These findings are particularly important to eliminate the extra processing steps to save time, energy and material maintaining the high quality of the final product.
Keywords: Additive manufacturing; Aluminum; Cryomilling; Light-weight alloys; Magnesium; Nano-composites